Metode Waterfall Untuk Meningkatkan Kualitas Layanan Nikah dan Rujuk Pada Kantor Urusan Agama (KUA) Kec.Lubuk Batu Jaya - Muhammad, Muhammad; Maria, Sinta; Gunawan, Vicky Setia; Mukhtar, Mukhtar (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The registration process for marriage and reconciliation is still carried out by submitting printed documents as requirements to the Office of Religious Affairs (Kantor Urusan Agama, KUA). The required documents for marriage registration include: Certificate of Marriage Eligibility, Spouse Consent Letter and Parental Consent Letter, Family Card (Kartu Keluarga), National ID (KTP), Latest Educational Diploma, Marriage Recommendation Letter (if coming from outside the local subdistrict), Birth Certificate, TT Immunization Certificate for women, Court Dispensation Letter (if the applicant is under 19 years old), Passport-sized photographs. These documents are submitted directly to the KUA subdistrict office through the Village Religious Counselor (Pembantu Penghulu), after which the officer records the registration in the marriage registration book. For reconciliation procedures, the applicant must appear with their former spouse and bring the necessary documents, which include: National ID (KTP), Family Card (Kartu Keluarga), Reconciliation Letter from the Village Head or Urban Ward Head, Original Divorce Certificate. The purpose of this study is to improve services at the KUA of Lubuk Batu Jaya Subdistrict by enhancing integrity, transparency, and cost certainty for the community. The methodology used in this study is the waterfall model, which is suitable for addressing issues related to marriage and reconciliation applications to make them faster and easier. Once the system is implemented, the result is an integrated system that simplifies the process. The application is tested using the black-box testing method, which examines the software from the perspective of functional specifications.